Poder de polícia ambiental e o princípio da prevenção - Schmidt, Cíntia (2012)
This work is scoped to address the environmental police power in the New Environmental Administrative Law , from the standpoint of the fundamental duty of environmental protection to good public administration. The first chapter addresses the issue of fundamental rights and duties of environmental protection, as well as environmental protection as a fundamental duty of good public administration. The second works with the police power of the environment, bringing up their characteristics and evolution in the "New Environmental Administrative Law." The third reflects on the impact of environmental principles in public administration, with emphasis on the precautionary principle. Still, it addresses the environmental police power in the sphere of jurisprudence, demonstrating how the judiciary has decided through this instrument. In this sense, it is emphasized that the principles of environmental law more specifically the principle of prevention - must be present in the core public administration, with a view that prevention should be the highest mark the completion of the New Administrative Law and Environmental inherently the fundamental right to an ecologically balanced and fundamental right to good public administration.